2000
DOI: 10.1021/jp001079x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the CH Groups in Dimethyl Sulfoxide Probed by NMR and IR

Abstract: 1H and 13C NMR of dimethyl sulfoxide (DMSO)/H2O mixtures were measured, together with the IR of DMSO/D2O mixtures, to study the effect of the polar SO group on hydration of the CH groups. Chemical shifts were determined by the external double reference method, which provides the in situ volume magnetic susceptibility indispensable to the correction of the chemical shifts. The chemical shift of the water protons as the measure of the polarization of the water in the mixtures, δ H 2O, increases from 3.6 ppm at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 17 publications
13
144
1
2
Order By: Relevance
“…They observed that the water clusters disappear between x s = 0.19 and 0.25, which is the concentration range, in which the Soret coefficient changes it's sign. The structural change is also supported by the NMR-study by Mizuno et al 34 which has been discussed in Sec. IV A.…”
Section: B Relation Between the Thermal Diffusion Motion And A Strucsupporting
confidence: 61%
See 1 more Smart Citation
“…They observed that the water clusters disappear between x s = 0.19 and 0.25, which is the concentration range, in which the Soret coefficient changes it's sign. The structural change is also supported by the NMR-study by Mizuno et al 34 which has been discussed in Sec. IV A.…”
Section: B Relation Between the Thermal Diffusion Motion And A Strucsupporting
confidence: 61%
“…There are numerous nuclear magnetic resonance (NMR) 34 , mass spectrometry 38 , dielectric spectroscopy 39 and x-ray scattering 40 studies, which investigate the change from the tetrahedral structure of water to other structures such as chain-like conformations with increasing solvent concentration. Takamuku et al 40 investigated alcohol/water solutions by X-ray scattering and found that the structure changes with increasing alcohol concentration in the order of n-propyl ≈ iso-propyl > ethyl > methyl at alcohol mole fractions of 0.1, 0.1, 0.2, and 0.3, respectively.…”
Section: B Relation Between the Thermal Diffusion Motion And A Strucmentioning
confidence: 99%
“…Table I) correlates with the concentration x ± solvent , where the Soret coefficient changes sign. [38][39][40] This observation has also been made for the Soret coefficient of poly(ethylenoxide) in the solvent mixture ethanol/water, which changes sign at x ethanol = 0.08. 29 This indicates that thermal diffusion is quite sensitive to changes in the fluid structure.…”
Section: Resultsmentioning
confidence: 58%
“…External double-reference method was used with a 530 µL external reference tube filled with tetramethylsilane (TMS). 26 Figure 2 shows the ATR-IR spectra of [ 4 ] have been studied, and the peaks were assigned in previous report. 9 For [BMIM][I], although the IR spectrum has not been reported as yet, the Raman spectroscopic study of [BMIM][Cl] could be consulted for peak assignment.…”
Section: Methodsmentioning
confidence: 99%